A Developing Model Of Relationship Among Service Quality, Consumer Satisfaction, Loyalty and Word of Mouth In Islamic Banking - Suryani, S.; Hendryadi, Hendryadi (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2015)
This  research  aims  to  develop  a  measurement  tool  of  service  quality  in  Islamic banking sector, and examine its relationship among satisfaction, word of mouth (WOM),  and  consumer  loyalty.  A  convenience  sampling  of  235  respondents collected  from  seven  locations  in  the  Lhokseumawe,  Aceh.  Partial  least  square -structural equation modeling- (PLS-SEM) was used to test the research hypotheses. The results revealed that the quality of service has four dimensions, they are: service portfolio and assurance/SPA, tangibles/TAN, reliability of communication/COM, and Islamic values/IVA. The PLS-SEM results suggest that SPA and COM are dominant factors affecting satisfaction, and satisfaction were significantly related to WOM and loyalty. Loyalty also positively and significantly related to WOM.DOI:10.15408/aiq.v7i1.1357